Il partito Fidesz tra regolamenti di conti interni e difesa degli interessi nazionali (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2020)
This essay aims to analyze the power system conceived by Viktor Orbán – the current Hungarian Prime Minister and historical leader of the Fidesz party – and his propaganda. To do so, all main topics of Orbán’s rhetoric will be examined: national sovereignty, the threat posed by migratory flows, the “enemies of the Homeland” – as George Soros – the fight against liberalism. Moreover, the conflict between Hungarian Government and the European Institutions will be described, as well as the confrontation between Fidesz party and the EPP. Fidesz originated in the late 80s as a progressive movement. In the first half of the following decade, though, it became a conservative party, following Viktor Orbán’s political calculations. Nowadays, it has become the tool for Orbán to take the lead of the European conservative field, ready to replace, if necessary, the EPP.
Keywords: Fidesz; Christian values; Illiberal regime; Liberalism; Rule of Law